2014
DOI: 10.1097/phh.0000000000000026
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Sun Safe Workplace Practices by Local Governments

Abstract: Context Outdoor workers are especially susceptible to skin cancer, the most common, but also one of the most preventable, forms of cancer. Colorado, the location of the study, has the second highest rate of skin cancer deaths in the nation. Objective Local government managers in Colorado—in municipalities, counties and special districts—were surveyed in order to ascertain the extent to which they engage in formal (written) and informal practices to protect their outdoor workers against excessive exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Although companies may include use of personal sun-protection practices in their institutional policies, few supply sun-protection equipment, and most existing policies do not explicitly state an intent to protect employees from excessive sun exposure (21). However, additional studies of local government organizations found that interventions that include personal contacts and theory-based training increased the likelihood of adoption of formal sun-protection policies and that adoption of sun-safe practices is not constrained by government budget or size (22,23). More research analyzing local, state, and national sun-safety policies is needed to understand their effects in both government and nongovernment organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Although companies may include use of personal sun-protection practices in their institutional policies, few supply sun-protection equipment, and most existing policies do not explicitly state an intent to protect employees from excessive sun exposure (21). However, additional studies of local government organizations found that interventions that include personal contacts and theory-based training increased the likelihood of adoption of formal sun-protection policies and that adoption of sun-safe practices is not constrained by government budget or size (22,23). More research analyzing local, state, and national sun-safety policies is needed to understand their effects in both government and nongovernment organizations.…”
Section: Discussionmentioning
confidence: 99%
“…311 In addition to employers, local governments and labor organizations have played a role in increasing programs for sun protection among outdoor workers. 312,313…”
Section: For Outdoor Work Settingsmentioning
confidence: 99%
“…Administrators in local government organizations closer to urbanized areas reported taking more steps to support sun protection of outdoor workers. 27 …”
Section: Discussionmentioning
confidence: 99%